2020
DOI: 10.1002/ppap.202000046
|View full text |Cite
|
Sign up to set email alerts
|

A concise overview on plasma treatment for application on textile and leather materials

Abstract: Plasma technology used for textile and leather materials treatment is a dry, environmental friendly, and easy to operate method by which surface modification is obtained without altering the bulk properties of the materials. Particularly, nonthermal plasmas are very appropriate due to the fact that most textiles, and especially leathers, are usually heat sensitive. The major objective of this review is to provide a critical update on the present state‐of‐art relating to plasma and its effects on different text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…A micro-dosing pump introduces the monomer into the reactor at 0.5 µL/s. The thermostatised treatment chamber allows the temperature to be raised during the plasma process, which increases the effectiveness of the deposition process [ 23 , 33 ]. ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A micro-dosing pump introduces the monomer into the reactor at 0.5 µL/s. The thermostatised treatment chamber allows the temperature to be raised during the plasma process, which increases the effectiveness of the deposition process [ 23 , 33 ]. ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gaidau et al also reported the use of cold plasma generated by dielectric barrier discharge (DBD) at atmospheric pressure and room temperature as a promising technique for dry reactivation and physical modification of collagen and keratin-based materials to improve complex characteristics, such as water repellence and flame retardancy [ 22 ]. Finally, a concise overview on plasma treatment for application on textile and leather materials was provided recently by Tudoran et al [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The IVCP may be subject to several distortions due to the measurement uncertainty that may arise from the physics of the phenomena involved in the measurement process. The two most important conditions that have to be taken into account in the IVCP measurement are the time involved in the measurement [14,36,51] and the possible contamination of the surface of the probe [53].…”
Section: Considerations On the Possible Distorsions On The Ivcpmentioning
confidence: 99%
“…Since then, the range of possible applications of plasma polymers rapidly increased, and plasma polymers are nowadays applied in such diverse areas as microelectronics, automotive, food packaging, textile industries, or in the biomedical field. They can act as separation, protective or barrier layers [ 4 , 5 , 6 , 7 , 8 ] or as films that modify the wettability or biofouling of coated objects [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%